12 Some Coordinates of The Contemporary Teacher Profile - Nadia Laura SERDENCIUC (Association of Social and Educational Innovation, 2015)
The present study outlines the role of the teacher's individual characteristics (the teacher viewed as a person) on the effectiveness of teaching. The professional knowledge, skills and attitudes need to be put in correspondence with personal traits in order to develop a reflective practice, to integrate innovation in teaching, to promote a competence-based learning process in a broader context of lifelong learning. A redefined relationship between the professional dimension and the personal dimension in the teacher's identity is essential for successfully fulfilling the educational mission of teachers related to the challenges of the 21st century.